2016
DOI: 10.1097/hjh.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between blood pressure variability, obesity, and left ventricular mechanics

Abstract: BP variability and LV deformation are significantly affected by obesity in untreated hypertensive patients. BP variability is associated with 2DE and 3DE LV mechanics independently of main clinical and echocardiographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
(39 reference statements)
0
11
0
1
Order By: Relevance
“…Investigations showed that patients with prehypertension, white‐coat hypertension, and masked hypertension also had significantly reduced multidirectional LV strain in comparison with normotensive controls . All studies agreed that blood pressure level correlated well with LV multidirectional strain and the strongest correlation was found for LV longitudinal strain. It was demonstrated that LV strain correlated well with blood pressure level independently of LV hypertrophy, LV diastolic function, body mass index, and age.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Investigations showed that patients with prehypertension, white‐coat hypertension, and masked hypertension also had significantly reduced multidirectional LV strain in comparison with normotensive controls . All studies agreed that blood pressure level correlated well with LV multidirectional strain and the strongest correlation was found for LV longitudinal strain. It was demonstrated that LV strain correlated well with blood pressure level independently of LV hypertrophy, LV diastolic function, body mass index, and age.…”
mentioning
confidence: 70%
“…Investigations confirmed that LV mechanics, and primarily longitudinal strain, was impaired in AH patients . The spectrum of patients with AH in the published studies was wider each year, and effect of common comorbidities such as obesity, diabetes, and metabolic syndrome on LV strain was stronger in AH patients than in patients with isolated AH, diabetes, or obesity . This showed that these risk factors had more synergistic negative effect than simple additive effect.…”
mentioning
confidence: 76%
“…BPV increases with bodyweight and possibly with insulin resistance. 20 Adult patients with arterial hypertension have higher systolic and diastolic BP, PP, and BPV. 21 Systolic BPV correlated with fasting glucose in children and adults.…”
Section: Blood Pressure Variabilitymentioning
confidence: 99%
“…Abdominal distribution of fat has a negative impact on blood pressure (BP), lipid metabolism, glucose tolerance or insulin resistance 3. Obesity correlates with left ventricular hypertrophy, and weight reduction is a factor restoring normal heart muscle mass 4. Cardiovascular risk is related to high BP, especially to isolated systolic hypertension as a cause of coronary heart disease and stroke 5 6.…”
Section: Introductionmentioning
confidence: 99%